HUBUNGAN ANTARA MAQĀṢID AL-SYARĪ’AH DENGAN BEBERAPA METODE PENETAPAN HUKUM (QIYĀS DAN SADD/FATH AL-ŻARĪ’AH) - Fatimah Halim (Hunafa: Jurnal Studia Islamika, 2010)
This article discusses the relationship between maqāṣid al-syarī'ah with several methods of  determining  the law. The object of the study is limited to two models of law, namely qiyās and  sadd (fath)  al-żarī'ah.  This problem was discussed through library research by using  the  comparative method. The results  showed that, the method of  determination of the law,  either through qiyās  and sadd (fatḥ)  al-żari'ah  have a very close relationship with maqāṣid al-syarīah. In the qiyās  method, maqāṣid al-syarī'ah is an important factor in assessing the illat, whereas in the method of al-żari'ah, maqāṣid al-syarī'ah  it is  sadd al-żarīah  or fath al-żarī'ah as a determinant factor.Kata Kunci: maqāṣid al-syarīah, qiyās, sadd al-żarī’ah, fatḥ al-żari’ah